(untitled) (Journal of Hama University, 2022)
The research aimed to identify the degree of application of the basic third-grade’ teachers for the principles of Active Learning from their Point of view in the city of Hama, and to identify the differences in the degrees of the members on the measurement of the Principles of Active Learning according to years of experience, scientific and educational qualification and training courses variables. The populations of the research reached (180) male and female teachers. The researcher used a descriptive approach , and a measurement of the Principles of Active Learning was applied as the objectives of the research which designed by (Al-Rushdi et sadah, 2017), and consisted of (44) statements. And that is after adapted to Syrian environment. The results of the study showed that the degree of the third-grade basic teachers’ application of the principles of active learning from their Point of view on was medium, and the results showed there were significant differences in their applications of active learning principals according to the scientific qualification and training courses variables, and there were no statistically significant differences in their applications of active learning principals according to the years of experience variable.